Oneness in the Laws of Social Norms and the Incoherence of Polytheism and Atheism - Laakel, Ayoub (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The research represents a scholarly endeavor to open a new dimension in the realm of social norms, deliberating on monotheism amidst the challenges of polytheism and atheism. It delves deeply into the study of the characteristics and attributes of social norms, recognizing their exclusive emanation from a singular divine source. The research problem is structured around resolving the debate within scientific circles that Allah alone cannot govern the human world independently; rather, there exist superior entities capable of influencing and altering destiny, sometimes substituting the divine with mythical entities or alternative systems. The primary objectives of the research include establishing the concept of Allah's unity and its manifestations within social norms. Utilizing a critical-analytical methodology, the study highlights the necessity for deeper exploration of social norms through various approaches. Each investigation, guided by scientific rigor and objectivity, inevitably concludes with a firm conviction in the excellence of Allah and His continuous governance of existence. Furthermore, both ancient and modern atheism face methodological crises in comprehending creation's origin, while polytheism acknowledges Allah's partial authority, yet perceives completeness only through associating additional forces to complement what they perceive as divine imperfections.